OBSERVING THE ACCESSABILITY OF DISABLED GROUPS IN MOSQUE: A CASE STUDY IN MATARAM CITY - Nazar Naamy (STIT Sunan Giri Bima, 2023)
This article tries to explain the practice of da’wah inclusion over disabled groups in houses of worship. The research using qualitative methods with a case study approach was carried out in Lombok and disability data was taken from